ANALISIS PEMBIAYAAN MURABAHAH PADA BANK MANDIRI SYARIAH KOTA SAMARINDA - Wahyuni, Sri (Journal of Innovation in Business and Economics, 2015)
This study aims to analyze about Murabahah financing at Mandiri syariah Bank in Samarinda city. Independent variables used in this study are inflation, the net operational margin, total assets and variables that reflect the type of Islamic bank financing policy. The dependent variable used in this study is the ratio of Islamic banks or financing problems in terms of so-called Non-Performing Financing (NPF). One of the results in this study was about Murabahah receivable for profit Loss sharing financing gave the most dominant effect toward Non Performing Finance Gross at Islamic Bank.